PROCES KARNY W MIASTACH POLSKICH (XVI–XVIII W.) – JEDNOŚĆ CZY WIELOŚĆ PROCEDUR? - Mikołajczyk, Marian (Zeszyty Prawnicze, 2016)
CRIMINAL PROCEDURE IN POLISH CITIES (IN THE 16TH – 18TH CENTURY) – UNITY OR MULTIPLICITY PROCEEDINGS? Summary In cities of Pre-partition Poland was in force law so-called German law, which in 16th-18th centuries was far removed from original Magdeburg law. Municipal law was created by the local legislation and court practice, that’s why systems of law of several cities were very different. These remarks refer especially to criminal proceedings, because there were so big diverse between cities, that’s we can ask about unity or multiplicity procedure. It seems after all that we can show some general rules for all cities and we should rather speak of unity of municipal criminal procedure.